Prognostic Value of Alactic Base Excess for 28 Day Mortality in Sepsis Patients: A Retrospective Prognostic Accuracy Study in an Intensive Care Unit - Sulistiono, Paulus; Sudjud, Reza Widianto; Budipratama, Dhany (Faculty of Medicine, Universitas Padjadjaran, 2025)
Introduction: Prognostication in sepsis is challenging. Serum lactate is widely used but cannot separate non-lactate contributions to metabolic acidosis. Alactic Base Excess (ABE) provides a more complete assessment of acid–base status. This study assessed ABE’s value in predicting 28-day mortality in sepsis patients.Methods: A retrospective study included 109 adult sepsis patients meeting Sepsis-3 criteria with arterial blood gas analysis within 24 hours of ICU admission. ABE was calculated from base excess and lactate. Prognostic performance was evaluated using ROC analysis, and association with mortality was assessed using odds ratios (OR).Results: Of 109 patients, 59 (54.1%) died within 28 days. Non-survivors had more negative median ABE than survivors (-7.04 vs. -0.15; p<0.001). Optimal ABE cut-off was ≤ -4.1. Patients with ABE ≤-4.1 had a higher risk of mortality (OR 38.6; 95% CI: 13.2–112.9; p<0.001).Discussion: ABE showed strong prognostic performance, reflecting non-lactate metabolic acidosis not captured by lactate alone. As it is derived from routine arterial blood gas analysis, ABE is practical for early risk stratification in critically ill sepsis patients.Conclusion: ABE demonstrates excellent prognostic value for 28-day mortality in ICU sepsis patients. An ABE ≤-4.1 is linked to significantly higher mortality and may serve as a readily available biomarker for early risk assessment and timely clinical decisions.